2016
DOI: 10.1007/s12253-016-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Expression of G2/M Transition Genes Reveals CDC25 Alteration in Nonfunctioning Pituitary Adenomas

Abstract: Dysregulation of G1/S checkpoint of cell cycle has been reported in pituitary adenomas. In addition, our previous finding showing that deregulation of Wee1 kinase by microRNAs together with other studies demonstrating alteration of G2/M transition in nonfunctioning pituitary adenomas (NFPAs) suggest that G2/M transition may also be important in pituitary tumorigenesis. To systematically study the expression of members of the G2/M transition in NFPAs and to investigate potential microRNA (miRNA) involvement. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
0
20
0
3
Order By: Relevance
“…Egy miRNS-nek a bá-zispárosodás szabályai szerint több célgénje is van, és egy célmolekula kifejeződését számos miRNS is szabályoz-hatja. A biológiai funkciók hátterében álló mechanizmusokat a sejten belüli jelátviteli útvonalakkal lehet a leginkább jellemezni, így a miRNS-ek szabályozó szerepét nemcsak egy-egy génhez (1. táblázat) [34,42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], hanem egy-egy jelátviteli útvonalhoz is lehet rendelni.…”
Section: A Mirns-ek áLtal éRintett Jelátviteli úTvonalak Az Agyalapimunclassified
See 2 more Smart Citations
“…Egy miRNS-nek a bá-zispárosodás szabályai szerint több célgénje is van, és egy célmolekula kifejeződését számos miRNS is szabályoz-hatja. A biológiai funkciók hátterében álló mechanizmusokat a sejten belüli jelátviteli útvonalakkal lehet a leginkább jellemezni, így a miRNS-ek szabályozó szerepét nemcsak egy-egy génhez (1. táblázat) [34,42,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], hanem egy-egy jelátviteli útvonalhoz is lehet rendelni.…”
Section: A Mirns-ek áLtal éRintett Jelátviteli úTvonalak Az Agyalapimunclassified
“…Kiegészítve és kiterjesztve korábbi vizsgálatainkat, szisztematikusan megvizsgálva a G2/M átmenetben részt vevő gének expressziójának szabályozását nem ACTH = adrenokortikotrop hormon; FSH = folliculusstimuláló hormon; GH = növekedési hormon; LH = luteinizáló hormon; NFA = nem funkcionáló, hormonálisan inaktív hypophysisadenoma; PRL = prolaktin funkcionáló agyalapimirigy-daganatokban, a 46 vizsgált gén közül számos eltérő expressziót mutatott, melyek közül a CDC25-család tagjainak miRNS-ek általi szabá-lyozására derült fény [46]. A CDC25-családba tartozó foszfatázok a CDK1-ciklin-B komplex defoszforilációja révén a G2/M ellenőrző ponton segítik a sejt mitózisba lépését.…”
Section: A Mirns-ek áLtali Sejtciklus-reguláció Agyalapimirigy-tumorounclassified
See 1 more Smart Citation
“…Adenoma tissues were removed by transsphenoideal surgery at the Hungarian National included immunostaining for anterior pituitary hormones (GH, PRL, ACTH, LH, FSH, SF1 and TSH) and staining for Ki-67 proliferation marker. All routine immunohistochemical studies were performed at the 1st Department of Pathology and Experimental Cancer Research, Semmelweis University, Budapest, Hungary as previously described [15,16]. Normal pituitary samples were obtained by autopsy within 6 h of death from patients with no evidence of any endocrine disease (University Clinical Centre, Belgrade, Serbia) [15].…”
Section: Samples and Rna Extractionmentioning
confidence: 99%
“…This later gene has been demonstrated that is expressed exclusively in the Rathke's pouch and adenohypophysis during the development of pituitary in both chicken and mouse embryos and not in the neuroectoderm (Proszkowiec-Weglarz et al 2011). By using these expressions it could be concluded that all pituitary samples used as normal contained all five adenohypophophysis specific cell types (data not shown) [15][16][17][18]. Tumor tissue specimens were immediately frozen in liquid nitrogen after the adenoma removal, and stored at -80 o C until use.…”
Section: Samples and Rna Extractionmentioning
confidence: 99%